The Demonic : Literature and Experience. - Fernie, Ewan (Taylor and Francis, 2013)
Are we either good or bad, and do we really know the difference? Why do we want what we cannot have, and even to be what we're not? Can we desire others without wanting to possess them? Can we open to others and not risk possession ourselves? And where, in these cases, do we draw the line?Ewan Fernie argues that the demonic tradition in literature offers a key to our most agonised and intimate experiences. The Demonic ranges across the breadth of Western culture, engaging with writers as central and various as Luther, Shakespeare, Hegel, Dostoevsky, Melville and Mann.>